A Legal Analysis of Gambling Practices within the Wara Ritual in North Barito Regency - Alzahra, Syezha Nayla Mutia; Wardhani, Novea Elysa; Pramita, Claudia Yuni (Dinasti Research, 2025)
This research aims to analyze the practice of gambling that occurs during the Wara Traditional Ceremony in Barito Utara Regency, as well as the law enforcement efforts made by the police regarding this issue. The Wara ceremony is part of the religious tradition of the Dayak Lawangan Hindu Kaharingan community, which aims to guide the souls of the deceased to the afterlife. However, the practice of gambling during this ceremony has deviated from its spiritual purpose, becoming a form of entertainment involving monetary bets. This conflicts with Indonesian positive law, particularly Article 303 of the Criminal Code (KUHP), which prohibits gambling. This study uses an empirical approach to explore how gambling practices take place in the ceremony and the challenges faced by the police in addressing it. The findings indicate that while gambling is considered part of a long-standing tradition, it cannot be justified under national law. Therefore, preventive efforts involving law enforcement, local government, and traditional leaders are necessary to address this issue. Legal education and the establishment of clear regulations are essential to maintain the balance between cultural preservation and law enforcement.